LINC00152 drives a competing endogenous RNA network in human hepatocellular carcinoma - Pellegrino, Rossella; Castoldi, Mirco; Ticconi, Fabio; Skawran, Britta; Budczies, Jan; Rose, Fabian; Schwab, Constantin; Breuhahn, Kai; Neumann, Ulf P.; Gaisa, Nadine T.; Loosen, Sven H.; Luedde, Tom; et al. (Cells, 2022)
Genomic and epigenomic studies revealed dysregulation of long non-coding RNAs in many cancer entities, including liver cancer. We identified an epigenetic mechanism leading to upregulation of the long intergenic non-coding RNA 152 (LINC00152) expression in human hepatocellular carcinoma (HCC). Here, we aimed to characterize a potential competing endogenous RNA (ceRNA) network, in which LINC00152 exerts oncogenic functions by sponging miRNAs, thereby affecting their target gene expression. Database and gene expression data of human HCC were integrated to develop a potential LINC00152-driven ceRNA in silico. RNA immunoprecipitation and luciferase assay were used to identify miRNA binding to LINC00152 in human HCC cells. Functionally active players in the ceRNA network were analyzed using gene editing, siRNA or miRNA mimic transfection, and expression vectors in vitro. RNA expression in human HCC in vivo was validated by RNA in situ hybridization. Let-7c-5p, miR-23a-3p, miR-125a-5p, miR-125b-5p, miR-143a-3p, miR-193-3p, and miR-195-5p were detected as new components of the potential LINC00152 ceRNA network in human HCC. LINC00152 was confirmed to sponge miR143a-3p in human HCC cell lines, thereby limiting its binding to their respective target genes, like KLC2. KLC2 was identified as a central mediator promoting pro-tumorigenic effects of LINC00152 overexpression in HCC cells. Furthermore, co-expression of LINC00152 and KLC2 was observed in human HCC cohorts and high KLC2 expression was associated with shorter patient survival. Functional assays demonstrated that KLC2 promoted cell proliferation, clonogenicity and migration in vitro. The LINC00152-miR-143a-3p-KLC2 axis may represent a therapeutic target in human HCC.
Gesehen am 27.06.2022